IMPLEMENTING RUSSIAN ARCTIC LNG PROJECTS IN A NEW GEOPOLITICAL LANDSCAPE: KEY CHALLENGES AND PROSPECTS - Mikhail V. Ulchenko (Север и рынок: формирование экономического порядка)
The European energy market is currently facing a paradox. On the one hand, European Union countries are actively pursuing sanctions aimed at limiting the development of the Russian energy sector. On the other hand, they are seeking to compensate for the sharp decline in pipeline gas supplies—particularly after the explosions damaging the Nord Stream and Nord Stream 2 pipelines—by increasing their imports of liquefied natural gas (LNG), including Russian-produced LNG. Meanwhile, Russian companies, notably Novatek and Gazprom, supported by the government, are striving to advance new LNG projects. Among these, the Arctic LNG 2 and Murmansk LNG projects are regarded as highly promising for successful implementation. This study identifies the leading LNG importers by the end of 2023, which include countries in the Asia-Pacific region—such as China, Japan, South Korea, India, and Thailand—along with EU countries like France and Spain. Key LNG exporters by the end of 2023 include the United States, Qatar, Australia, and Russia. The purpose of this study is to analyze the state of the global LNG market under the new geopolitical conditions and to explore the challenges and prospects for the implementation of Russian Arctic LNG projects. The study’s scientific contribution lies in assessing the potential for new domestic LNG projects and identifying the needs of energy companies for gas tankers. The next phase of the research will involve evaluating the prospects for the sale of LNG from Russia, the United States, and Qatar to Asia-Pacific and European Union markets.